Modern approaches to social and hygienic monitoring of the health status of drivers of public transport - Babienko, V.V.; Gwantzeladze, C.R.; Sidorenko, S.G. (Актуальні проблеми транспортної медицини, 2015)
The aim of the study was to develop a system of social and hygienic monitoring of the health status of drivers of shuttle buses. The research was performed during the 2009-2014. Working conditions of drivers of shuttle buseswere evaluated. The assessment of the health status of shuttle buses drivers using objective methods of clinical and physiological, psycho-physiological and laboratory research was conducted. There was shown that existing system of pretrip and afterinspection is imperfect, run formally and requires improvement. There was developed database which includes records about health conditions and risk factors of occupational environment.The developed integrated system of social-hygienic monitoring is discussed as able to reduce car accidents and improve drivers’ health. Метою дослідження була розробка системи соціально-гігієнічного моніторингу стану здоров’я водіїв маршрутних таксі Дослідження проведено в 2009-2014 р. Вивчалися умови праці водіїв маршрутних таксі. Зроблена оцінка стану здоров’я водіїв маршрутних таксі з використанням методів клініко-фізіологічного, психофізіологічного і лабораторного дослідження. Показано, що існуюча система передрейсових та післярейсових медичних оглядів недосконала, проводиться формально і вимагає удосконалення. Створена база даних включає записи про стан здоров’я та фактори ризику виробничого середовища. Обговорюється можливість зниження числа дорожньо-транспортних пригод та поліпшення стану здоров’я водіїв за допомогою розробленої системи соціально-гігієнічного моніторингу. Целью исследования была разработка системы социально-гигиенического мониторинга состояния здоров’я водите лей маршрутных такси. Исследование проведено в 2009-2014 г. Изучались условия труда водителей маршрутных такси. Произведена оценка состояния здоровья водителей маршрутных такси с пользованием методов клинико-физиологического, психофизиологического и лабораторного исследования. Показано, что существующая система предрейсовых и послерейсовых медицинских осмотров несовершенна, проводится формально и требует усовершенствования. Созданная база данных включает записи о состоянии здоровья и факторах риска производственной среды. Обсуждается возможность снижения числа дорожно-транспортных происшествий и улучшения состояния здоровья водителей с помощью разработанной системы социально-гигиенического мониторинга.